(untitled) (Bangladesh Journal of Agricultural Research, 2013)
The study was conducted at the farmers pond at Sadar Upazilla of Bagerhat District, South-west coastal region of Bangladesh during the period from May 2006 to April 2007 to understand the present status of crop rotation practice and assess the production and cost benefit ratio of the existing culture practices. Two treatments viz., the crop rotation with paddy (T1) and the shrimp-prawn-fish culture (T2) were used in the studies. Shrimp (Penaeus monodon), prawn (Macrobrachium rosenbergii), and catla (Catla catla) were stocked at 20000, 10000, and 250 individuals/ha, respectively, in both treatments. In T1, aquaculture phase was from May to December 2006, and the episode of paddy (BRRI dhan 28) cultivation was initiated after full harvest of aqua products and continued till April. Similar farm inputs were given for the common components in both the treatments. Shrimps were harvested four months following stocking in both T1 and T2 treatments.. In T1, production of shrimp, prawn, and catla were 347.20, 355.35, and 140.4 kg/ha, respectively and in T2, productions were 354.38, 432.37, and 204.7 kg/ha, respectively. In T1, total paddy production was 6200 kg/ha. Net benefit in T1 and T2 was Tk. 300,477 and Tk. 262,561/ha, respectively. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16924 Bangladesh J. Agril. Res. 38(3): 389-399, September 2013